SISTEM INFORMASI MANAJEMEN PADA BISNIS - Agung Wijoyo; Ahmad Bajuri; Andini Gustiani; Aulia Safira Putri; Eka Wahyuningsih; Silviyawati (Journal of Research and Publication Innovation, 2023)
Management Information Systems in business are used to solve or provide solutions to business problems such as production costs, services, or applied business strategies. With this Management Information System, it is hoped that a company or business can anticipate and understand economic opportunities in implementing new information technology. A business or company will also be assisted in ensuring the quality and skills of human resources in utilizing it. In addition, with this Management Information System access to data that has been provided accurately and in real time, company or business owners can develop plans that are more optimal and effective in analyzing the implementation of program policies and identifying needs to support information systems that have been developed.